Analisis dan Perancangan Sistem Informasi Manajemen Penjadwalan Praktikum Menggunakan Algoritma Genetika di Laboratorium Fakultas Teknologi Pertanian Universitas Jambi - Nata, Rudi; Siahaan, Kondar (LPPM Universitas Dinamika Bangsa, 2018)
Practicum scheduling is a matter of allocating time, courses, lecturers, and laboratory rooms. At the Laboratory of the Agricultural Technology Faculty, Jambi University (FTP UNJA), practicum scheduling is still done manually. This study aims to design a practical scheduling information management system in the laboratory of the Faculty of Agricultural Technology, Jambi University. Based on the characteristics of the problems that occur in practicum scheduling, genetic algorithms are suitable methods to solve them by representing the problem components into chromosomes and evaluated based on scheduling constraints that have been created so as to produce an optimal practicum schedule. The scheduling optimization process using genetic algorithms will go through a chromosome representation process, population initialization, fitness calculation, selection, crossover and mutation. The results of the study successfully designed a practicum scheduling information system in prototype form. The system design uses Data Flow Diagram which can be implemented into a practicum scheduling management information system at the FTP UNJA Laboratory.